Towards Knowledge-based Systems for GDPR Compliance - O'Sullivan, Declan; Lewis, David; PANDIT, HARSHVARDHAN JITENDRA (My University, 2018)
Legal compliance is traditionally seen to be sufficiently demonstrable using legal documents that describe how various operations and activities follow a given set of obligations. The General Data Protection Regulation (GDPR) enforces larger responsibilities upon organisations and provides motivation for the use of technological measures that can ease its compliance. While there is no legal requirement to collaborate on compliance technologies or to use a common mechanism for defining knowledge, doing so has several benefits to the larger community. Through this paper, we describe how open and shared technologies targeted towards GDPR and its compliance can be used to create knowledge-based systems. Our approach uses semantic web technologies due to their open and exible nature towards describing concepts and relationships. We present a model for such a knowledge-based system along with work published to date.
Contextualised Knowledge Graphs (CKG), International Semantic Web Conference (ISWC)
Keywords: GDPR; Knowledge-based system; Legal compliance graph; Legal compliance; Provenance; Consent; Linked data; Semantic web; Digital Engagement; Knowledge and data engineering